2018
DOI: 10.3389/fmicb.2018.03086
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Aerosolization and Drying on the Viability of Pseudomonas syringae Cells

Abstract: Airborne dispersal of microorganisms influences their biogeography, gene flow, atmospheric processes, human health and transmission of pathogens that affect humans, plants and animals. The extent of their impact depends essentially on cell-survival rates during the process of aerosolization. A central factor for cell-survival is water availability prior to and upon aerosolization. Also, the ability of cells to successfully cope with stress induced by drying determines their chances of survival. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Another explanation might be due to the metagenomic approach that allows to sample both living and dead cells. Aerosolization has been shown to be particularly stressful and even lethal for microorganisms (Alsved et al, 2018;Thomas et al, 2011). The functional potential from the dead cells in air might have a greater weight on the overall functional potential observed and lead to the dilution of the functional potential of the actual living cells that have adapted to atmospheric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation might be due to the metagenomic approach that allows to sample both living and dead cells. Aerosolization has been shown to be particularly stressful and even lethal for microorganisms (Alsved et al, 2018;Thomas et al, 2011). The functional potential from the dead cells in air might have a greater weight on the overall functional potential observed and lead to the dilution of the functional potential of the actual living cells that have adapted to atmospheric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric processes of aerosolization, the properties of surrounding landscapes, the lifting of air beyond the boundary-layer to enable long-range transport of microbes from their source regions, the survival of microorganisms in changing temperature regimes of clouds or the ability to survive temperature extremes, as well as desiccation or nutrient limitation, are all factors impacting the composition and dispersion of aerosolized microbes (Möhler et al, 2007;Burrows et al, 2009;Bowers et al, 2011;Xia et al, 2013;Bianco et al, 2016;Carotenuto et al, 2017;Alsved et al, 2018;Evans et al, 2019;Tignat-Perrier et al, 2019). Bertolini et al (2013) suggested meteorological factors together with the chemical composition of the airborne particulate matter as well as the air mass sources as driving factors for airborne microbial variability at ground level.…”
Section: Introductionmentioning
confidence: 99%
“…A range of processes, such as aerosolisation (Alsved et al 2018), vapor to liquid phase change, particle coalescence, in-cloud circulation, temperature regime, cloud lifetime, cloud trajectories, nucleation properties and local air composition at the site of precipitation, effect on the microbial composition of precipitation (Möhler et al 2007).…”
Section: Introductionmentioning
confidence: 99%